Adaptation Of The Food Craving Questionnaire-Trait Into Turkish - Sadiye Akkurt; Gizem Kose; Aslihan Donmez (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi, 2019)
We aimed to evaluate psychometric features, factor structure and internal consistency of the Turkish version of Food Craving Questionnaire-Trait Scale and to determine its validity. The study was completed with 302 individuals. Sample group includes students-teachers who are at 18-65 age range, have different occupational groups and generally serve at Ministry of National Education and of school administrations. The questionnaires used comprise form of demographical data, food craving scale (including 39 articles) and eating attitudes test (including 40 articles). 39 articles and 9 sub-dimensions of Food Craving Scale were studied by confirmatory factor analysis and it was determined that factor loads and error variances of all articles are proper but fit indexes are not at allowable levels. Reliability and validity studies of Food Craving Scale were carried out using confirmatory factor analysis AMOS 22.0 program and total item correlation, Cronbach Alpha and equivalent (parallel) form reliability tests were carried out using SPSS 15.0 program. Two unpaired sample t tests and one-way analysis of variance (ANOVA) were used in comparison by variables. Significance level was determined as0, 05 (p [JCBPR 2019; 8(2.000): 69-80]